Antibacterial Activity and Wound Healing of Excision Gel of Ethanol Extract of Sintrong (Crassochepallum crepidioides)(Benth.) S. Moore.) Leaves in Mice Infected Staphylococcus aureus - Candrika Candrika; Aminah Dalimunthe; Hakim Bangun (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Crassochepallum crepidioides (Benth.) S. Moore.) is a plant demonstrated to be effective in wound treatment, empirically and experimentally. contain secondary metabolites, which contribute to the wound healing process. Further research is required to scientifically validate the antibacterial wound healing properties of sintrong leaf ethanol gel. This study aimed to empirically validate the antibacterial efficacy of a gel formulation derived from the ethanol extract of sintrong leaves. Excision wound healing assessments were conducted using the sintrong leaf ethanol extract gel on excision wounds infected Staphylococcus aureus. Phytochemical screening, the formulation of ethanol extract gel concentrations 10%, 20%, 30%, antibacterial activity testing of the ethanol extract gel. Excision wound healing activity with a depth 1 mm a width of 2 cm. The wound became infected treatment was administered for 15 days to monitor the decrease in wound diameter on days 0, 3, 5, 10, 15 indicated that the ethanol could be formulated and satisfied the preparation evaluation criteria. Ethanol extract gel has antibacterial properties against Staphylococcus aureus. The study on excision wound healing indicated that an increased concentration of extract gel correlates with a greater percentage of healing. On day 10 the healing percentages of the 30% gel and Bioplacenton were similar at 80%. On day 15 the percentages of 30% gel and Bioplacenton were almost equal 30% gel being 98.50%. Bioplacenton being 99.50% and histopathological assay revealed elevated collagen, fibroblast, and angiogenesis levels corresponding to the increasing concentration of the preparation.